Skilling digital technologies in the labour sphere: experience of empirical research in Minsk and Saint Petersburg - Titarenko, Larissa G.; Karapetyan, Ruben V. (Journal of the Belarusian State University. Sociology, 2021)
Article is written on the basis of an analysis of empirical data obtained in 2021 from sociological studies conducted in Saint Petersburg and Minsk – cities with a population of one million, which served as the object of research of the current digital transformation. A feature of both samples was the large percentage of people with higher education among the employed population. In fact, we studied a group of urban professionals. The authors identify trends in the world of work that detail digital transformation processes. The purpose of the article is to describe the trends in the digitalisation process in the world of work in a large city and to reveal how relevant these trends are for the Belarusian and Russian professionals. The authors show the level of digital acquisition of the employed urban population today, as well as the impact on this process of the previous year associated with the pandemic and the inevitable transition of a part of the employed population to remote work. The article presents the factors that determine the labour motivation of urban professionals of different levels in their mastering of information and communication technologies, reveals the development trends of labour digitalisation processes and their impact on certain groups of professionals employed in both production and non-production spheres. It is concluded that the motivation of the employed population to master new digital knowledge directly depends on how much a person needs it in the workplace, contributes to his career advancement or helps to keep the workplace.